Production and characterization of enzyme-treated spray-dried soursop (Annona muricata L.) powder - Chang, Lee Sin; Karim, Roselina; Abdulkarim, Sabo Mohammed; Mohd Ghazali, Hasanah (Wiley, 2018)
Easily perishable soursop (Annona muricata L.) fruit was converted into powder for value‐addition. Soursop puree obtained from fruit pulp that had been treated with different concentrations (0–2% v/w) of Celluclast 1.5 L at fixed (1.5% v/w) concentration of Pectinase Ultra SP‐L were spray‐dried at various inlet temperatures (130–160 °C) after mixing the puree with maltodextrin (20–40% w/w). Multiple responses optimization from Response Surface Methodology (RSM) indicated puree that was pretreated with 1.3% (v/w) cellulase and incorporated with 37% w/w maltodextrin and spray‐dried at an inlet temperature of 156 °C could be transformed into powder that had the following physicochemical properties: moisture content, 2.03% (wb); Aw, 0.18; hygroscopicity, 29.02 g/100g; stickiness, 173.02 g and yield 70.56% of powder. The glass transition temperature (Tg) was found to range between 46.53 and 58.25 °C, indicating the spray‐dried powder was an amorphous material. Surface morphology of the powder particles, viewed using Scanning Electron Microscopy, showed they exhibited spherical in shape and possessed a continuous wall (crust) without surface cracks.